The Effect of Good Corporate Governance On Company Value With Profitability As Variable Intervening - Hawaldi, Muhamad; Hifni, Syaiful; Oktaviani, Ayu (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The study was purpose to examine and analyze the effect of good corporate governance on firm value with profitability as an intervening variable. Research is included in explanatory research. As population is general banking listed on the Indonesia Stock Exchange for 2018-2020 period as many as 45 banks. Sampling technique with purposive sampling obtained a sample size of 29 banks. The unit of analysis is the financial statement and annual reports of general banking companies. Data analysis using path analysis with hypothesis testing using t test. Results of hypothesis testing using path analysis showed that good corporate governance has a significant effect on firm value. Good corporate governance has a significant effect on profitability-ROA. Profitability-ROA has a significant effect on firm value. Sobel test results found that the variable Profitability-ROA does not mediate the effect of good corporate governance has a significant effect on firm value. As conclusion there is an effect of good corporate governance on profitability and firm value. However, the Profitability-ROA variable does not mediate the effect of good corporate governance, which has a significant effect on firm value.